Servizi educativi 0-6 e digitale, dopo la pandemia: riflessioni pedagogiche - Di Bari, Cosimo (Studi sulla Formazione/Open Journal of Education, 2022)
The Covid-19 pandemic, since March 2020, has "challenged" early childhood education services, forcing them to work for a long period in emergency: regulations to contain the contagion have forced education professionals in the zero-to-six age group to rethink the educational relationship by downsizing the role of physical contact, revising spaces, methodologies and routines. Both during the closure of services (in 2020) and in the following two years, the use of digital technologies has been a necessity in order to be able to maintain contact with children (first) and families (later): the contribution, starting from the analysis of some experiences, reflects on the challenges opened up by the emergency and the new perspectives that are being inaugurated with a view to integrating digital experiences alongside traditional ones within educational services.